1999
DOI: 10.1086/302656
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a Gene for Duane Retraction Syndrome to Chromosome 2q31

Abstract: Duane retraction syndrome (DRS) is a congenital eye-movement disorder characterized by a failure of cranial nerve VI (the abducens nerve) to develop normally, resulting in restriction or absence of abduction, restricted adduction, and narrowing of the palpebral fissure and retraction of the globe on attempted adduction. DRS has a prevalence of approximately 0.1% in the general population and accounts for 5% of all strabismus cases. Undiagnosed DRS in children can lead to amblyopia, a permanent uncorrectable lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 36 publications
1
58
0
5
Order By: Relevance
“…This deletion on chromosome 2 is B5 Mb distal to the published locus for Duane retraction syndrome type 2 (DURS2), mapped by linkage analysis to 2q31. 29 Maybe the deletion is associated with an inversion disrupting the DURS2 gene. In case 4 with severe autism and self-destructive behaviour, a terminal deletion on 2q was found, a region previously found to be deleted in autistic patients.…”
Section: Mapping Of Chromosome Imbalances By Cgh H Lybaek Et Almentioning
confidence: 99%
“…This deletion on chromosome 2 is B5 Mb distal to the published locus for Duane retraction syndrome type 2 (DURS2), mapped by linkage analysis to 2q31. 29 Maybe the deletion is associated with an inversion disrupting the DURS2 gene. In case 4 with severe autism and self-destructive behaviour, a terminal deletion on 2q was found, a region previously found to be deleted in autistic patients.…”
Section: Mapping Of Chromosome Imbalances By Cgh H Lybaek Et Almentioning
confidence: 99%
“…A large dominant pedigree with isolated DA led to the identification of the DURS2 locus on chromosome 2 [Appukuttan et al, 1999;Evans et al, 2000], although the DURS2 gene has not yet been identified. Both DA and HGP can also occur in association with other congenital anomalies including skeletal defects, limb and digit dysplasia, scoliosis, and facial weakness Kirkham 1970;Pfaffenbach et al, 1972;Verzijl et al, 2003].…”
Section: To the Editormentioning
confidence: 99%
“…Autopsy examination of two patients with Duane anomaly has shown hypoplasia of the VI nerve nucleus and absence of the VI nerve on the affected side, the ipsilateral lateral rectus being innervated by branches of the third nerve [Hotchkiss et al, 1980]. The prevalence is approximately 0.1% in the general population, and Duane anomaly accounts for 5% of all cases of strabismus [Appukuttan et al, 1999]. Up to 10% of cases are familial and follow an autosomal dominant pattern of inheritance.…”
Section: Introductionmentioning
confidence: 99%